The Effect Of Saltwater Concentration On Saltwater Lamp Efficiency Using Different Types Of Fuel Cell - Loganaayagi, M Ganesunn (2023)
The aim of this research is to prepare to develop a saltwater lamp and study the effect of concentration of saltwater and seawater that impacts the efficiency of the saltwater lamp. Lighting is a basic essential thing to all the community. For the entire community, lighting is a basic necessity. Even though Malaysia is a developing nation with a wealth of fossil fuels, electrifying the entire nation remains a significant problem. Malaysia starts the developing renewable energy sources to get around this. This is in contradiction to Malaysia's 2005 plan. To reduce the negative environmental impact of conventional electricity supply and prepare for future energy demands, Malaysia has made a strong shift toward effective energy management, sustainable energy use, and the deployment of renewable energy. This initiative is entirely focused on SDG 7: Ensure that everyone has access to modern, cheap, dependable energy. The development of saltwater lamps is a parallel endeavour to make Malaysia a carbon neutral country by 2050. The evolution of using fuel cell technology-based lamps is beneficial for individuals in rural, isolated, Orang Asli, and Felda communities. This study focuses on the different concentration levels of saltwater efficiency on a different type of saltwater-fuel cell lamp. Among the concentration of seawater, 10g, 15g, 20g and 30g. . Through the analysis, the results of measuring the conductivity of seawater and saltwater solution at various concentrations in the initial of the project show that the conductivity values and the saltwater concentration have a linear relationship whereby the conductivity value increases as the concentration of saltwater increases. The 20g shows the utmost performance in both Al-Air Fuel Cell and Al-Cu Fuel Cell. However, Al-Air Fuel Cell shows greater performance with 20g of saltwater concentration and has the highest current density of 210.47 mA/cm2 with power density of 6067.19 W/m2. In conclusion, the concentration of 20g with Al-Air Fuel Cell is the best environmentally friendly option to illuminate for more than 24 hours. Lastly on the testing of durability it founds that the aluminum plate had lost almost 6.21g and copper plate 0.06g at end of the experiment. Due to the properties of Aluminium electrodes Al electrodes experienced the highest reduction in weight after being immersed and run the test in the 350 ml of saltwater and seawater for overall total testing 101.5 hours hours. The electroplate is predicted to have a lifetime to last up to 150 hours before it needs to be replaced if it is turned on continuously. Therefore, it is safe to conclude that the electrodes can produce electricity for at least 6 days.